Assessments of ionic release and biocompatibility of Co-Cr and CP-Ti produced by three different manufacturing techniques. (March 2022) - Hu, Qin; Liu, Yuan; Pan, Yu; Wang, Yinghui; Jiang, Lei; Lin, Honglei; Cheng, Yiling; Xu, Caiming; Lin, Donghong; Cheng, Hui
Abstract: As the development of digital technology, it is necessary to assess the impacts of different manufacturing techniques on the chemical stability and biocompatibility of Co-Cr alloys and commercially pure titanium (CP-Ti). Human gingival fibroblasts were cultured on the specimens of Co-Cr and CP-Ti manufactured via either lost-wax casting (casting), computer numerical controlled milling (milling) or selective laser melting (SLM) for various periods prior to biocompatibility evaluations including cell viability assay, inflammatory cytokine expression and immunofluorescence cellular morphology. The ionic release levels were assessed by inductively coupled plasma mass spectrometry. The results indicated that: first, digitally fabricated (milling and SLM) Co-Cr groups exhibited significant lower ionic release levels and better biocompatibility than casting group ( P < 0.05), and the milling Co-Cr group showed the best performance. Second, no statistically significant differences were observed in ionic release and biocompatibility among CP-Ti groups fabricated by different methods ( P > 0.05). Meanwhile, the cell viability, morphology, density and chemical stability of all CP-Ti groups were significantly better than that of all Co-Cr alloys ( P < 0.05). Third, the total ion concentrations and the single ion release levels of Co, W and Mn exhibited significant correlations with the biocompatibility of Co-Cr alloys. These results demonstrate that digital manufacturing techniques (milling and SLM) can be considered as ideal alternatives to the traditional lost-wax casting method. Graphical Abstract: ga1 Highlights: Digitally manufactured (milling and SLM) Co-Cr exhibit better chemical stability and biocompatibility than casting one. Ion release levels and biocompatibility of CP-Ti are not affected by the manufacturing methods. There are significant correlations between ion release levels and biocompatibility of Co-Cr alloys. Digitally manufacturing techniques can be considered as ideal alternatives to the traditional lost-wax casting method.